Le retour de Lyon sous l'autorité royale à la fin des guerres de Religion (1593-1597) - Hours, Henri (Chrétiens et Sociétés. Documents et Mémoires, 2020)
Henri Hours' book on the end of the League in Lyon is one of the most important works of 16th century historiography in Lyon, although very few readers have had the opportunity to consult it. This is its main paradox and the challenge of this edition. The thesis was defended at the École Nationale des Chartes in 1951, but it has never been published and, in accordance with the rules of the École, it has never been made available. Only those who knew the author were able to read it, which does not prevent it from appearing in all bibliographies concerning the Wars of Religion. Following his death in 2017 and with the agreement of his family, the Collection Chrétiens & Sociétés has decided to publish this memoir for the first time in order to make it accessible to the public in Lyon and to historians of religious confrontations. Henri Hours meticulously analysed the last years of the League at Lyon, the crucial years 1593-1597. Since 1589, the city had swayed to the side of Catholic intransigence to the point of rejecting its sovereign, Henry IV, and maintaining a costly but necessary war effort in a region crossed by denominational borders. The bishop, Pierre d'Epinac, the consuls of Lyon, the governor of the city, the Savoyard and Spanish spies, but also the street preachers and the little people who were very inclined to be alarmed, were the main actors in these events. Here we touch on the political and religious dimensions of urban history. Through municipal deliberations, correspondence, pamphleteering and some contemporary accounts, Henri Hours unravels the skein of the city's political shift towards submission to the king. By looking back at the writings of some of these actors, notably Pierre Mathieu and Claude de Rubys, he also questions the memory of the event in the consciousness of Lyon.